Development of new and efficient transformation methods in plants using Agrobacterium remains - Dantata F. Mustafa; Kubi G. Markaw; Ahmed N. Ali (Global Journal of Plant and Soil Sciences, 2017)
Plant genetic engineering has become one of the most important molecular tools in modern crop breeding. Significant progress has been made in the development of new and efficient transformation methods in plants. Agrobacterium remains one of the predominant microbes employed in this approach. In particular, progress in Agrobacterium –mediated transformation of varieties of agricultural plants such as cereals, legumes and other crop plants has led to emergence of transgenic – enabling technologies, including generation of marker genes, gene targeting, and chromosomal engineering. This recent advancement has boosted agricultural biotechnology by augmenting the conventional plant breeding methods to achieve improved yield and quality of crops, hence production of economic crops in commercial quantity. Agricultural biotechnology has reduced crop losses from pest and diseases, improved the nutrient efficiency of food and animal feeds, reduce post harvest losses with increased shelf life of fruits and vegetables, and increased the stress tolerance of crop plants allowing them to tolerate various environmental extremes such as cold and drought.